S1417CD: A Prospective Multicenter Cooperative Group-Led Study of Financial Hardship in Metastatic Colorectal Cancer Patients. (4th January 2022) - Shankaran, Veena; Unger, Joseph M; Darke, Amy K; Suga, Jennifer Marie; Wade, James L; Kourlas, Peter J; Chandana, Sreenivasa R; O'Rourke, Mark A; Satti, Suma; Liggett, Diane; Hershman, Dawn L; Ramsey, Scott D
Abstract: Background: Financial toxicity is a growing problem in oncology, but no prior studies have prospectively measured the financial impact of cancer treatment in a diverse national cohort of newly diagnosed cancer patients. S1417CD was the first cooperative group-led multicenter prospective cohort study to evaluate financial hardship in metastatic colorectal cancer (mCRC) patients. Methods: Patients aged 18 years or older within 120 days of mCRC diagnosis completed quarterly questionnaires for 12 months. We estimated the cumulative incidence of major financial hardship (MFH), defined as 1 or more of increased debt, new loans from family and/or friends, selling or refinancing home, or 20% or more income decline. We evaluated the association between patient characteristics and MFH using multivariate cox regression and the association between MFH and quality of life using linear regression. Results: A total of 380 patients (median age = 59.9 years) were enrolled; 77.7% were White, 98.0% insured, and 56.5% had annual income of 50 000 or less. Cumulative incidence of MFH at 12 months was 71.3% (95% confidence interval = 65.7% to 76.1%). Age, race, marital status, and income (split at 50 000 per year) were not statistically significantly associated with MFH. However, income less than 100 000 and total assets less than 100 000 were both associated with greater MFH. MFH at 3 months was associated with decreased social functioning and quality of life at 6 months. Conclusions: Nearly 3 out of 4 mCRC patients experienced MFH despite access to health insurance. These findings underscore the need for clinic and policy solutions that protect cancer patients from financial harm.